THE CHALLENGES OF TAX REFORM AND TAX EDUCATION IN ANGOLA 2012-2024 - Pascoal, Alberto da Silva (Seven Editora, 2025)
The aim of this article is to analyze how tax reform and tax education make the revenue collection system more efficient. The specific objectives of the tax reform are to define the concepts and principles of tax reform, to demonstrate the importance of tax education and to analyse the main challenges and benefits of tax reform. In this perspective, its theoretical foundation was based on the available literature substantiated by the deductive method with a qualitative approach, dealing with a theoretical and bibliographic review. Tax reform and tax education bring to the educational area a proposal based on the development of man as a citizen, seeking to be a new tool for the development of the country. DOI: https://doi.org/10.56238/sevened2024.037-219